Training Graphic Design to Improve Student Creativity - Ujianto, Nur Tulus (ASEAN Journal of Empowering Community, 2024)
Pangkah 1 Public High School, is an educational institution that provides formal education, Pangkah 1 Public High School located at Jl. Raya Kalikangkung, Pangkah District, Tegal Regency, with a distance of ± 15 Km from the Tegal Pancasakti University campus. Computer subjects given to students at SMA Negeri 1 Pangkah are still limited to basic computer knowledge. Armed with this basic knowledge, of course, students must redevelop their creativity in the digital world. The extracurricular provided by SMA Negeri 1 Pangkah is only in sports, scouts and music. Therefore, students at SMA Negeri 1 Pangkah as a millennial generation must be able to take advantage of the digital world to be able to improve their abilities so that they can be used as one of the provisions in facing competition in the world of work later. Besides that, SMA Negeri 1 Pangkah does not yet have a graphic design subject, so community service activities are carried out to hold a graphic design themed training for 1 day. Through this community service program, it is hoped that it can increase student creativity in knowledge and graphic design skills. The results showed that the participants were very enthusiastic in participating in this graphic design training activity. Participants can get to know graphic design and can practice the applications used to make the graphic design.